2021
DOI: 10.3389/fnins.2021.674576
|View full text |Cite
|
Sign up to set email alerts
|

Neural Infection by Oropouche Virus in Adult Human Brain Slices Induces an Inflammatory and Toxic Response

Abstract: Oropouche virus (OROV) is an emerging arbovirus in South and Central Americas with high spreading potential. OROV infection has been associated with neurological complications and OROV genomic RNA has been detected in cerebrospinal fluid from patients, suggesting its neuroinvasive potential. Motivated by these findings, neurotropism and neuropathogenesis of OROV have been investigated in vivo in murine models, which do not fully recapitulate the complexity of the human brain. Here we have used slice cultures f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 78 publications
(106 reference statements)
0
12
0
Order By: Relevance
“…Using sliced cultures from an adult human brain, Almeida and colleagues investigated OROV infection of mature human neural cells, which resulted in the release of TNF-α (pro-inflammatory cytokine tumour necrosis factor-alpha) and the reduction of cell viability and tissue damage in a 48-h period post-infection, which could generate further neuronal dysfunctions and neurological symptoms in human infections. Although OROV infects both neurons and microglia, the latter were the preferred central nervous system (CNS) cells infected by the virus, again demonstrating that OROV infection may lead to neuronal complications, as microglia cells are the primary defence cells in the CNS that might even serve as viral reservoirs in the brain [ 160 ]. OROV infection has also been studied in human blood mononuclear cells, and results demonstrated that T CD4+ lymphocytes (Jurkat cells) were more susceptible to infection than other lymphoid lineages.…”
Section: Omic’s Study Across Members Of Bunyavirales Order— ...mentioning
confidence: 99%
“…Using sliced cultures from an adult human brain, Almeida and colleagues investigated OROV infection of mature human neural cells, which resulted in the release of TNF-α (pro-inflammatory cytokine tumour necrosis factor-alpha) and the reduction of cell viability and tissue damage in a 48-h period post-infection, which could generate further neuronal dysfunctions and neurological symptoms in human infections. Although OROV infects both neurons and microglia, the latter were the preferred central nervous system (CNS) cells infected by the virus, again demonstrating that OROV infection may lead to neuronal complications, as microglia cells are the primary defence cells in the CNS that might even serve as viral reservoirs in the brain [ 160 ]. OROV infection has also been studied in human blood mononuclear cells, and results demonstrated that T CD4+ lymphocytes (Jurkat cells) were more susceptible to infection than other lymphoid lineages.…”
Section: Omic’s Study Across Members Of Bunyavirales Order— ...mentioning
confidence: 99%
“…Astrocytes may similarly contribute to the cellular HIV reservoir (Lutgen et al, 2020; Valdebenito et al, 2021). The emerging RNA viruses Oropouche virus and Middle Eastern respiratory syndrome coronavirus infect neurons and glia in humanized mice or human brain slice cultures, leading to complement‐mediated BBB changes and microglial activation (Almeida et al, 2021; Jiang et al, 2021). Future studies will determine whether these effects are also observed in human patients.…”
Section: Microglial Activation Affects Neuroinvasive Viral Clearance ...mentioning
confidence: 99%
“…Eastern respiratory syndrome coronavirus infect neurons and glia in humanized mice or human brain slice cultures, leading to complementmediated BBB changes and microglial activation (Almeida et al, 2021;Jiang et al, 2021). Future studies will determine whether these effects are also observed in human patients.…”
Section: Microglial Activation Affects Neuroinvasive Viral Clearance ...mentioning
confidence: 99%
“…In all donors, the tissue collected was mapped as excluded from the epileptogenic zone. Our group has previously employed this experimental model to model molecular events associated with Alzheimer's disease (Mendes et al., 2018; Sebollela et al., 2012; Vasconcelos et al., 2021) and viral neuroinfection (Almeida et al., 2021; Crunfli et al., 2022; Figueiredo et al., 2019). We demonstrate that human brain slices preserve the human CNS complexity in terms of cell types found in vivo, validating our previous observations (Almeida et al., 2021; Crunfli et al., 2022; Figueiredo et al., 2019; Mendes et al., 2018; Sebollela et al., 2012; Vasconcelos et al., 2021).…”
Section: Introductionmentioning
confidence: 99%